ISU-ISU KUNCI UJARAN KEBENCIAN (HATE SPEECH): IMPLIKASINYA TERHADAP GERAKAN SOSIAL MEMBANGUN TOLERANSI - Mohammad Iqbal Ahnaf; Suhadi Suhadi (Harmoni, 2014)
Hate speech has become a serious ‘challenge’ for Indonesia’s democratization process. Political openness has allowed various forms of speech and writing with a variety of messages; this has included narratives that encourage hostility toward other groups. Hate speech is frequently associated with the occurrence of violent acts against religious minorities. The demand for the government to act decisively against hate speech is getting stronger. However, the prohibition of hate speech in Indonesia is not a simple thing. Many people have expressed concern that enforcing a law against hate speech will recreate the repression of the past era where SARA was used to suppress political opposition. Additionally, defining hate speech and regulating it is also controversial. This paper is an initial effort to start a discussion about policy options to deal with the threat of hate speech, either by the state or by social movements. This paper describes dangerous forms of hate speech for a multicultural democratic country like Indonesia, the conceptualization of hate speech, laws in Indonesia related to hate speech and the experiences of a number of democratic western countries in dealing with hate speech. Finally, this paper proposes actions can be done by social movements to respond to hate speech.